Extraction of proteins from natural rubber latex wastewater for metal removal and its antimicrobial properties / Hairani Tahir - Hairani , Tahir (2022)
Natural rubber latex plant waste from a centrifuge process contains hev protein. However, these proteins are mostly allergenic. The precipitation process carried out to purified protein from the waste bulk at different pH conditions, namely, from pH 3 to pH 8. The purpose of varying pH condition was to capture specific proteins. Amount of protein collected at different pH measured and it found that greater amounts collected at pH 4 and pH 7. Precipitation also carried out without the use of ammonium sulphate compare the amount of protein collected. Overall, the amount of protein collected from the salt-free condition was lesser by 25 %. The purified protein was then isolated using polyarcryl amide gel Biorad P-60 gel via open column chromatography. Each isolate containing protein introduced to SDS PAGE electrophoresis using benchmark protein marker as a standard to identify the isolated protein. Amongst the proteins isolated, seven types found to match the molecular weight of 20 kDa hevea protein to 40 kDa. Isolated protein was characterized using FTIR to countercheck the existence of protein for the particular isolate and using UV at 280 nm and 595 nm to estimate the concentration of protein in each number of isolates. Each isolate containing protein freeze-dried for storage purposes. Powder samples were more convenient to carry about and occupied smaller space compared to liquid samples, which were more susceptible to degradation or putrefaction, especially at warmer temperatures. The identified proteins were cross-matched with the hevea protein databank proposed earlier and used according to its specific function. At first, Hevein, hev b6, one of the isolated proteins, intended for antifungal study and mangan superoxide dismutase, Hev b10 for metal extraction study, but the limited amount of proteins collected meant that the overall study of precipitated protein undertaken, instead. Freeze-dried precipitated proteins analyzed for traces of metal and it was found that by using AAS, about 2 ppm of copper and 4 ppm of lead were recorded. However, many samples was saved by using ICP and additionally, 254 ppm zinc, 0.013 ppm aluminum, 0.129 ppm of selenium, 0.001 ppm nickel, 0.749 of ferum and 19.7 ppm of magnesium were detected. Proteins collected from different purification techniques exposed to 2 ppm, 5 ppm, 10 ppm, and 20 ppm sets of metal ion concentration to study their binding capability. Results showed that as the concentration of protein was increased, the metal removal intensity was also increased. It also observed that the binding capability differed between metals.